The Efficacy of Buccal Infiltration of 4% Articaine and PSA Injection of 2% Lidocaine on Anesthesia of Maxillary Second Molars - Maljaei, Ensiyeh; Pourkazemi, Maryam; Ghanizadeh, Milad; Ranjbar, Rana (Iranian Endodontic Journal, 2017)
Introduction: During the early mixed dentition period, the location of the deciduous maxillary second molar results in ineffectiveness of the infiltration technique in this area. In such cases, administration of posterior superior alveolar (PSA) nerve block is recommended; however, such a technique has some complications. The present study was undertaken to compare the effects of buccal infiltration of 4% Articaine and PSA technique with 2% Lidocaine on the success of anesthesia of maxillary deciduous second molars in 6 to 9-year old children. Methods and Materials: In the present double-blind randomized clinical trial, 56 children aged 6-9 years requiring vital pulp therapy of deciduous maxillary second molar were included. In group 1, 4% Articaine was injected using a buccal infiltration technique. In group 2, 2% Lidocaine was injected using the PSA nerve block technique. After 10 min, the caries was removed and access cavity preparation was instituted. The patients were asked to report the presence or absence of pain during the procedure. Therefore, the existence of pain was measured by the patient’s self-report. Data were analyzed with descriptive statistical methods and the chi-squared test. Results: Pain was reported by 6 (21.4%) and 9 (32.1%) subjects in the Articaine and Lidocaine groups, respectively. Chi-squared test did not reveal any significant differences between the two groups (P=0.54). Conclusion: Under the limitations of the present study, there was no significant differences between the results of Articaine buccal infiltration and Lidocaine PSA technique, so Articaine buccal infiltration can be used as a substitute for the PSA technique. Keywords: Articaine; Buccal Infiltration Technique; Deciduous Second Molar; Lidocaine; Posterior Superior Alveolar Nerve Block